2013
DOI: 10.4236/health.2013.512a009
|View full text |Cite
|
Sign up to set email alerts
|

Images of sorrow—Experiences of losing a co-twin in old age

Abstract: What it is like when a lifelong twin relationship ends through death in later life is the focus of this study. It draws on interview data from seven twins who are part of a longitudinal Swedish twin study (SATSA) and who lost their co-twins in old age. Data were analyzed using qualitative latent content analysis. The results showed that the experience of loss of the co-twin was profound, including an emotional as well as a behavioral dimension. Loss and loneliness were expressed as the dominant feelings relate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 42 publications
1
6
0
Order By: Relevance
“…Consequently, when exposed to a co-twin death, both the grief (i.e., emotional reactions) and confusion of identity may contribute to a profound and long-lasting vulnerability of surviving twins. Indeed, in line with previous literature describing intense grief of surviving twins after co-twin loss ( Segal and Ream, 1998 ; Rosendahl and Björklund, 2013 ), in the present study, we showed that the subsequent risk of developing first-diagnosed psychiatric disorders increased by 55–65% in the twin population, after carefully controlling for familial factors. Of note, such risk elevation was most obvious during the first month (7-fold), but persistently existed more than 10 years after the loss.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Consequently, when exposed to a co-twin death, both the grief (i.e., emotional reactions) and confusion of identity may contribute to a profound and long-lasting vulnerability of surviving twins. Indeed, in line with previous literature describing intense grief of surviving twins after co-twin loss ( Segal and Ream, 1998 ; Rosendahl and Björklund, 2013 ), in the present study, we showed that the subsequent risk of developing first-diagnosed psychiatric disorders increased by 55–65% in the twin population, after carefully controlling for familial factors. Of note, such risk elevation was most obvious during the first month (7-fold), but persistently existed more than 10 years after the loss.…”
Section: Discussionsupporting
confidence: 92%
“…With regard to psychiatric reactions to a co-twin death, only a handful of descriptive studies with small sample sizes have been conducted, mainly using self-reported measures of grief (i.e. sorrow or general sadness) as an outcome ( Segal et al, 1995 ; Segal and Ream, 1998 ; Rosendahl and Björklund, 2013 ). Evidence on a potential rise in rates of clinically diagnosed psychiatric disorders associated with the loss of a co-twin is, however, totally lacking.…”
Section: Introductionmentioning
confidence: 99%
“…Most of the literature centered around the loss of a twin in utero, at birth, or as a young child. I found 14 articles written in the latter 1900s and early 2000s that related to my area of interest and mirrored my feelings and questions (Segal, 2019;Rosendahl et al, 2013;McIlroy, 2010;Segal, 2009;Tomassini et al, 2003;Withrow & Schweibert, 2005;Macdonald, 2002;Segal & Ream, 1998;Woodward, 1988;Segal et al, 1995;Segal & Bouchard, 1993;Nichols & Bibro, 1966). Four topics provided insight into my experience.…”
Section: Insights From Literature Review On Twin Lossmentioning
confidence: 72%
“…While accumulating evidence supports that both childhood and adult twin loss are associated with increased risk of psychiatric morbidity among the surviving twins ( Rosendahl SP and Björklund, 2013 ; Segal and Ream, 1998 ), no previous study has addressed whether such emotional reactions can be observed after a very early co-twin loss where limited twin relationship, perception, or memory from the loss could be expected. The absence of evidence is mainly due to the complexity of the research question and lack of high-quality data to address potential confounding by multiple factors, such as twin pregnancy and birth (i.e., suboptimal birth characteristics) but a singleton-like life, familial factors, and genetic susceptibility to diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Our recent findings suggest an increased risk of psychiatric disorders after a loss of co-twin, compared to loss of a full (non-twin) sibling, beyond age 2 ( Song et al, 2020 ). The greater risk increase after loss of a co-twin might be due to the stronger emotional bond between twins ( Rosendahl SP and Björklund, 2013 ; Segal and Ream, 1998 ) and the greater genetic relatedness, in the case of monozygotic twins ( Segal and Ream, 1998 ; Parkes, 1993 ; Neyer, 2002 ). In contrast, with cognitive immaturity and limited (or no) afterbirth interactions, a co-twin loss at birth or during the neonatal period leaves little room for a twin bond to be established and therefore it seems implausible that the mental health of the surviving twin would be affected by such a loss.…”
Section: Introductionmentioning
confidence: 99%